A method for producing lightweight concrete blocks for walls from vanadium-titanium ore slag

CN120664848BActive Publication Date: 2026-10-09SIPING MODERN IRON & STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510860162.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-25
Publication Date
2026-10-09
Estimated Expiration
2045-06-25

AI Technical Summary

Technical Problem

[0004]鉴于上述的分析,本发明旨在提供一种采用钒钛矿渣生产墙体用轻质混凝土砌块的方法,用以解决现有技术中轻质混凝土砌块的制备过程复杂、成本难以控制的问题

Benefits of technology

[0024] A) The method for producing lightweight concrete blocks for walls provided by this invention uses vanadium-titanium slag as the main raw material. By using inexpensive vanadium-titanium slag to replace some traditional raw materials, it can not only effectively solve the environmental problems caused by the accumulation of vanadium-titanium slag, realize the resource utilization of industrial solid waste, improve resource utilization rate, and effectively reduce the production cost of lightweight concrete blocks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120664848B_ABST
    Figure CN120664848B_ABST
Patent Text Reader

Abstract

The application discloses a method for producing light-weight concrete blocks for walls by using vanadium-titanium ore slag, and belongs to the technical field of building material preparation, aiming at solving the problems of complicated preparation process and uncontrollable cost of light-weight concrete blocks in the prior art. The method comprises the following steps: putting vanadium-titanium ore slag and grinding aids into a ball mill for grinding treatment; adding cement, lime, gypsum, aluminum powder, foam stabilizer and vanadium-titanium ore slag into a stirrer for mixing and stirring to obtain mixed powder; mixing the aluminum powder with the foam stabilizer and then adding water to obtain a suspension; after the mixed powder and water are mixed and stirred to obtain uniform slurry, the suspension is added for continuous stirring, so that the aluminum powder is uniformly dispersed in the slurry; the slurry is poured into a mold for standing and gas evolution to obtain a green body; and the green body is cut to obtain light-weight concrete blocks. The application can be used for the production of light-weight concrete blocks for walls.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of building material preparation technology, and in particular relates to a method for producing lightweight concrete blocks for walls using vanadium-titanium slag. Background Technology

[0002] Lightweight concrete blocks possess excellent properties such as light weight, thermal insulation, heat insulation, and sound insulation, making them an ideal new type of wall material widely used in the construction industry. Vanadium-titanium ore slag is a solid waste generated during the smelting of vanadium-titanium magnetite. Large-scale accumulation of slag not only occupies land resources but may also cause environmental pollution.

[0003] Currently, although there have been attempts to apply slag to building materials, the utilization rate of vanadium-titanium slag in the production of lightweight concrete blocks is low due to the processing technology, which fails to fully realize its potential value. Furthermore, the preparation process is complex and the cost is difficult to control. Summary of the Invention

[0004] In view of the above analysis, the present invention aims to provide a method for producing lightweight concrete blocks for walls using vanadium-titanium slag, so as to solve the problems of complex preparation process and difficult cost control of lightweight concrete blocks in the prior art.

[0005] The objective of this invention is mainly achieved through the following technical solutions.

[0006] This invention provides a method for producing lightweight concrete blocks for walls using vanadium-titanium ore slag, comprising the following steps:

[0007] Step 1: Weigh the raw materials, which include vanadium-titanium slag, cement, lime, gypsum, aluminum powder, and foam stabilizer.

[0008] Step 2: Place the vanadium-titanium ore slag and grinding aid into a ball mill for grinding;

[0009] Step 3: Add cement, lime, gypsum, aluminum powder, foam stabilizer, and the vanadium-titanium slag obtained in Step 2 into a mixer and mix to obtain a mixed powder;

[0010] Aluminum powder is mixed with a foam stabilizer and then water is added to obtain a suspension.

[0011] Step 4: After mixing the powder and water to obtain a uniform slurry, add the suspension and continue stirring to ensure that the aluminum powder is evenly dispersed in the slurry;

[0012] Step 5: Pour the slurry obtained in Step 4 into the mold and let it stand to generate gas, so that the slurry expands to form a blank with uniform pores;

[0013] Step 6: Cut the blank to obtain lightweight concrete blocks.

[0014] Furthermore, in step 1, the particle size of the vanadium-titanium slag is less than 0.15 mm.

[0015] Furthermore, in step 1, the cement is silicate cement with a strength grade of not less than 42.5.

[0016] Furthermore, in step 1, the effective calcium oxide content of the lime is not less than 80%.

[0017] Furthermore, in step 2, the mass ratio of grinding aid to vanadium-titanium slag is 3-5:100.

[0018] Furthermore, in step 3, dry mix for 3 to 5 minutes.

[0019] Furthermore, in step 4, the mass ratio of the mixed powder to water is 40-50:100.

[0020] Furthermore, in step 5, the temperature for allowing the gas to rise is 20℃~30℃.

[0021] Furthermore, in step 5, the relative humidity is 60%–80%.

[0022] Furthermore, the standing time for gas generation is 1 to 2 hours.

[0023] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0024] A) The method for producing lightweight concrete blocks for walls provided by this invention uses vanadium-titanium slag as the main raw material. By using inexpensive vanadium-titanium slag to replace some traditional raw materials, it can not only effectively solve the environmental problems caused by the accumulation of vanadium-titanium slag, realize the resource utilization of industrial solid waste, improve resource utilization rate, and effectively reduce the production cost of lightweight concrete blocks.

[0025] B) The method for producing lightweight concrete blocks for walls provided by the present invention improves the activity of vanadium-titanium slag and enhances its compatibility with other raw materials by grinding vanadium-titanium slag.

[0026] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained through the embodiments described and the accompanying drawings, which are particularly pointed out. Attached Figure Description

[0027] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.

[0028] Figure 1 A flowchart of a method for producing lightweight concrete blocks for walls using vanadium-titanium slag, provided in Embodiment 1 of the present invention;

[0029] Figure 2 This is a schematic diagram of the slag mold structure during the spray cooling of medium-titanium type blast furnace slag with a slag shell on the surface in the method for producing lightweight concrete blocks for walls using vanadium-titanium slag provided in Embodiment 1 of the present invention.

[0030] Figure 3 This is a schematic diagram of the slag mold structure during the demolding of solid slag blocks in the method for producing lightweight concrete blocks for walls using vanadium-titanium slag provided in Embodiment 1 of the present invention.

[0031] Figure label:

[0032] 1-Mold cavity; 2-Coolant circulation pipe; 3-Inner baffle; 4-Coolant supply unit; 5-Coolant connection pipe; 6-Water supply magnetic sleeve; 7-Water supply magnetic ring; 8-Unloading plate; 9-Longitudinal motor; 10-Rotating magnetic sleeve; 11-Rotating magnetic ring. Detailed Implementation

[0033] The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, which constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.

[0034] This invention provides a method for producing lightweight concrete blocks for walls using vanadium-titanium ore slag, see [link to relevant documentation]. Figure 1 It includes the following steps:

[0035] Step 1: Weigh the raw materials according to the proportions. The raw materials include vanadium-titanium slag, cement, lime, gypsum, aluminum powder and foam stabilizer (e.g., sodium dodecylbenzene sulfonate).

[0036] Step 2: Put the vanadium-titanium slag and grinding aid into a ball mill for grinding to improve the activity of the vanadium-titanium slag.

[0037] Step 3: Add cement, lime, gypsum, aluminum powder, foam stabilizer, and vanadium-titanium slag obtained in Step 2 into a mixer and mix them. Dry mix for 3 to 5 minutes until fully mixed and homogeneous to obtain a mixed powder.

[0038] Aluminum powder is mixed with a foam stabilizer and then water is added to obtain a suspension.

[0039] Step 4: Mix the powder and water for 4 to 7 minutes to obtain a uniform slurry, then add the suspension and continue stirring for 1 to 2 minutes to ensure that the aluminum powder is evenly dispersed in the slurry. The mass ratio of the powder to water is 40 to 50: 100.

[0040] Step 5: Pour the slurry obtained in Step 4 into the mold and let it stand to generate gas, so that the slurry expands to form a blank with uniform pores;

[0041] Step 6: Use a cutting machine to cut the blank to the required size to obtain blank blocks of the predetermined specifications.

[0042] Compared with the prior art, the method for producing lightweight concrete blocks for walls of the present invention, on the one hand, uses vanadium-titanium slag as the main raw material, and uses the low-cost vanadium-titanium slag to replace part of the traditional raw materials. This not only effectively solves the environmental problems caused by the accumulation of vanadium-titanium slag, but also realizes the resource utilization of industrial solid waste, improves the resource utilization rate, and effectively reduces the production cost of lightweight concrete blocks.

[0043] On the other hand, grinding vanadium-titanium slag can improve its activity and compatibility with other raw materials.

[0044] For example, in order to ensure the strength of lightweight concrete blocks, the raw materials in step 1 above include, by mass, 50 to 70 parts of vanadium-titanium slag, 15 to 25 parts of cement, 10 to 20 parts of lime, 3 to 8 parts of gypsum, 0.05 to 0.15 parts of aluminum powder, and 0.01 to 0.05 parts of foam stabilizer.

[0045] The vanadium-titanium slag has a particle size of less than 0.15 mm, the cement is silicate cement with a strength grade of not less than 42.5, and the lime has an effective calcium oxide content of not less than 80%.

[0046] In this way, through reasonable raw material ratio, the prepared lightweight concrete blocks have a good pore structure, a compressive strength of 5MPa to 8MPa, a thermal conductivity of less than 0.15W / (m·K), and excellent thermal insulation performance.

[0047] In order to reduce the content of ferromagnetic impurities in vanadium-titanium ore slag and improve the quality of lightweight concrete blocks, the following steps are included between step 1 and step 2:

[0048] Magnetic separation is performed on vanadium-titanium ore slag to remove ferromagnetic impurities.

[0049] To further improve the surface activity of vanadium-titanium ore slag, for example, in step 2 above, the mass ratio of grinding aid to vanadium-titanium ore slag is 3-5:100, the grinding aid consists of triethanolamine and ethylene glycol in a mass ratio of 1-1.5:2, the grinding time is 3-5 hours, and the specific surface area of ​​the vanadium-titanium ore slag after grinding is 400 m². 2 / kg~500m 2 / kg.

[0050] For example, in step 5 above, the temperature for static gas generation is 20℃~30℃, the relative humidity is 60%~80%, and the static gas generation time is 1h~2h.

[0051] To ensure the stability of the billet block, the following steps are included after step 6 above:

[0052] Step 7: The green block is fed into the autoclave and pressurized to 1.2MPa-1.5MPa at a rate of 0.1MPa / h-0.2MPa / h. It is then maintained at this pressure for 6-8 hours for autoclaving.

[0053] Step 8: Depressurize to atmospheric pressure at a rate of 0.1MPa / h to 0.2MPa / h, remove the billet from the autoclave, and obtain concrete blocks.

[0054] Understandably, in order to obtain vanadium-titanium slag, the following steps are included before step 1 above:

[0055] Step a: Direct the liquid titanium-type blast furnace slag discharged from the blast furnace directly into the slag mold;

[0056] Step b: Air-cool the medium-titanium blast furnace slag in the slag mold for 3 to 5 minutes to form a slag shell on the surface of the liquid medium-titanium blast furnace slag in the slag mold. The thickness of the slag shell is 20 mm to 35 mm, which serves as an isolation layer. The interior of the medium-titanium blast furnace slag in the slag mold is still liquid blast furnace slag. Limiting the thickness of the slag shell within the above range can ensure that the slag shell has a certain mechanical strength and will not soften during the subsequent reheating process. At the same time, it can resist the spraying force generated by the spraying during the subsequent spraying process, ensuring that the slag shell will not crack and avoiding direct contact between the spraying water and the liquid blast furnace slag.

[0057] Step c: Spray cooling the medium-titanium blast furnace slag with slag shell on the surface for 30 min to 60 min, so that the liquid blast furnace slag inside the medium-titanium blast furnace slag in the casting slag mold is completely solidified, and a solid slag block is obtained.

[0058] Step d: Crush the solid slag to obtain vanadium-titanium ore slag.

[0059] In this way, on the one hand, the combination of air cooling and spray cooling can produce dense and high-strength vanadium-titanium slag. Specifically, air has a low specific heat capacity (about 1 kJ / kg·K) and no phase change, so it mainly relies on convective heat transfer and has a slow cooling rate. Air cooling is a slow cooling method, which can promote the crystallization of the surface of the medium-titanium blast furnace slag in the slag mold and form a slag shell, avoiding thermal stress that could cause the slag shell to crack. This slag shell can also serve as an isolation layer to prevent the subsequent spray cooling water from directly contacting the liquid medium-titanium blast furnace slag in the slag mold and producing water-quenched slag (which has lower strength and more pores), thus ensuring the density and high strength of the obtained vanadium-titanium slag.

[0060] On the other hand, water has a high specific heat capacity (4.18 kJ / kg·K) and a fast heat transfer rate, which can quickly reduce the temperature of liquid blast furnace slag. Spray cooling is a fast cooling method. Through spray cooling, effective heat transfer can be achieved between the spray cooling water and the liquid titanium-type blast furnace slag under the slag shell. With the slag shell as the base layer, a crystalline layer is formed layer by layer downwards, ensuring the uniformity of crystallization of the solid slag block formed, thereby ensuring the density and high strength of the obtained vanadium-titanium ore slag.

[0061] On the other hand, the liquid titanium-type blast furnace slag discharged from blast furnace 6 can be directly poured into the slag mold and then directly carried out subsequent processing. There is no need to transport the high-temperature liquid titanium-type blast furnace slag, which can effectively improve the processing safety of liquid titanium-type blast furnace slag and simplify the processing flow.

[0062] Considering that spray cooling can only transfer heat from above the slag mold, through the slag shell and the liquid blast furnace slag inside the medium-titanium blast furnace slag within the mold, it may result in a slow cooling rate and poor cooling uniformity for the liquid blast furnace slag inside the medium-titanium blast furnace slag. Therefore, the structure of the slag mold specifically includes a mold cavity 1, a coolant circulation pipe 2, and an internal baffle 3, see [reference needed]. Figure 2 The coolant circulation pipe 2 is located inside the mold cavity 1 and its axis is perpendicular to the bottom wall of the mold cavity 1. For example, the axis of the coolant circulation pipe 2 is arranged in the vertical direction. The top of the coolant circulation pipe 2 is closed and the bottom is open. The inner baffle 3 is located in the coolant circulation pipe 2 and is arranged along the axis of the coolant circulation pipe 2. There is a gap between the top of the inner baffle 3 and the top of the coolant circulation pipe 2, dividing the hot straight pipe into an inlet rectangular pipe, a top connecting pipe and an outlet rectangular pipe connected in sequence.

[0063] In this way, while spray cooling is being performed, cooling water is supplied to the cooling liquid circulation pipe 2. The cooling water flows through the inlet rectangular pipe, the top connecting pipe, and the outlet rectangular pipe. Through the pipe wall of the cooling liquid circulation pipe 2, heat is transferred to the liquid vanadium-titanium smelting slag inside the medium-titanium type vanadium-titanium smelting slag in the molding mold. At the same time, the spray water transfers heat through the slag shell to the liquid vanadium-titanium smelting slag inside the medium-titanium type vanadium-titanium smelting slag in the molding mold. This enables heat exchange from both the surface and the interior of the liquid vanadium-titanium smelting slag, improving the uniformity and efficiency of cooling.

[0064] Understandably, in order to supply cooling water to the coolant circulation pipe 2, the above-mentioned equipment also includes a coolant supply unit 4 and a coolant connection pipe 5. The coolant connection pipe 5 includes a symmetrically arranged water supply rectangular pipe and a drain rectangular pipe, which together form a rectangular coolant connection pipe 5. The inlet end of the water supply rectangular pipe is connected to the outlet of the coolant supply unit 4, and the outlet end of the water supply rectangular pipe is sealed to the inlet rectangular pipe. The inlet end of the drain rectangular pipe is sealed to the outlet rectangular pipe, and the outlet end of the drain rectangular pipe is connected to the inlet of the coolant supply unit 4.

[0065] To prevent water leakage during water supply, the above-mentioned equipment also includes a water supply magnetic sleeve 6 and a water supply magnetic ring 7. The bottom of the coolant circulation pipe 2 protrudes from the bottom of the mold cavity 1. The water supply magnetic ring 7 is located at the bottom of the mold cavity 1. The bottom of the coolant circulation pipe 2 passes through the bottom of the mold cavity 1 and the water supply magnetic ring 7 and protrudes from the water supply magnetic ring 7. The water supply sealing sleeve is fitted on the outer wall of the coolant connecting pipe 5 and is slidably connected to the coolant connecting pipe 5.

[0066] When the molding die moves to the bottom of the spray unit, and the coolant circulation pipe 2 and the coolant connection pipe 5 are positioned accordingly, the water supply magnetic sleeve 6 is energized and magnetically attracted to the water supply magnetic ring 7, causing the water supply magnetic sleeve 6 to move towards the coolant circulation pipe 2 and be fitted onto the connection between the coolant circulation pipe 2 and the coolant connection pipe 5, thus achieving a sealed connection between the two and preventing water leakage during the water supply process.

[0067] For easier demolding of solid slag blocks, see [link / reference]. Figure 3 The coolant circulation pipe 2 can be used to achieve rapid demolding of solid slag blocks. Specifically, the inner cavity of the molding mold is cubic, the outer wall of the coolant circulation pipe 2 is threaded, and the outer wall of the threaded structure is cylindrical. The above-mentioned discharge unit includes a discharge plate 8 and a discharge reciprocating motor. The output end of the discharge reciprocating motor is connected to the discharge plate 8.

[0068] When demolding and unloading are required, the coolant circulation pipe 2 is rotated. Due to the presence of the threaded structure and the internal limit of the cubic cavity of the forming mold, the solid slag can only move upward, thereby detaching from the cavity of the forming mold and achieving demolding. Then, the unloading reciprocating motor is turned on, and the unloading reciprocating motor drives the unloading plate 8 to push the solid slag away from the top of the forming mold, so that the solid slag falls into the crushing component for crushing.

[0069] Understandably, in order to drive the rotation of the coolant circulation pipe 2, the above-mentioned equipment also includes a longitudinal motor 9. When the molding die moves to the top of the discharge unit, the output shaft of the longitudinal motor 9 is fixedly connected to the bottom of the coolant circulation pipe 2. The longitudinal motor 9 drives the coolant circulation pipe 2 to rotate, thereby realizing the demolding of the solid slag block.

[0070] To prevent interference with the output shaft of the longitudinal motor 9 during the movement of the molding die, the aforementioned equipment also includes a rotating magnetic sleeve 10 and a rotating magnetic ring 11. It should be noted that the water supply magnetic ring 7 and the rotating magnetic ring 11 can be the same annular structure. The magnetic sleeve is fitted onto the outer wall of the output shaft of the longitudinal motor 9 and is slidably connected to the output shaft. The cross-sectional shape of the inner wall of the magnetic sleeve and the cross-sectional shape of the output shaft of the longitudinal motor 9 are both rectangular. Thus, when the molding die moves to the bottom of the discharge unit, and the coolant circulation pipe 2 corresponds to the position of the output shaft of the longitudinal motor 9, the rotating magnetic sleeve 10 is energized and magnetically attracted to the rotating magnetic ring 11. This causes the rotating magnetic sleeve 10 to move towards the coolant circulation pipe 2 and fit onto the bottom of the coolant circulation pipe 2, achieving a fixed connection between the coolant circulation pipe 2 and the output shaft of the longitudinal motor 9.

[0071] Example 1

[0072] Raw material preparation: Weigh out 50 parts by weight of vanadium-titanium slag, 25 parts of cement, 15 parts of lime, 5 parts of gypsum, 0.1 parts of aluminum powder, and 0.03 parts of foam stabilizer; wherein, the particle size of vanadium-titanium slag is less than 0.15mm, the cement is 42.5 grade silicate cement, and the effective calcium oxide content of lime is 82%.

[0073] Vanadium-titanium ore slag pretreatment: Magnetic separation is performed on the vanadium-titanium ore slag to remove ferromagnetic impurities; the magnetically separated vanadium-titanium ore slag is then placed in a ball mill, and a grinding aid (triethanolamine to ethylene glycol in a mass ratio of 1:2) at 3% of the vanadium-titanium ore slag mass is added. The mixture is ground for 3 hours to achieve a specific surface area of ​​400 m². 2 / kg.

[0074] Raw material mixing: Add the pretreated vanadium-titanium slag, cement, lime, and gypsum to the mixer and dry mix for 3 minutes. Then add water equal to 40% of the total mass of the materials and mix for 5 minutes to make a slurry.

[0075] Aluminum powder and foam stabilizer treatment: Mix aluminum powder and foam stabilizer, add water to make a suspension, add it 1 minute before the slurry is completely stirred, and continue stirring for 1 minute.

[0076] Casting and gas generation: Pour the slurry into the mold and let it stand for 1 hour at a temperature of 20℃ and a relative humidity of 60%.

[0077] Cutting: After the gas generation is completed, cut the blank according to the specifications.

[0078] Autoclaving: The green body is placed in an autoclave, pressurized to 1.2 MPa at a rate of 0.1 MPa / h, maintained for 6 hours, and then depressurized at a rate of 0.1 MPa / h to obtain lightweight concrete blocks. Testing showed that the block has a compressive strength of 5.2 MPa and a thermal conductivity of 0.14 W / (m·K).

[0079] Example 2

[0080] Raw material preparation: Weigh out 60 parts by weight of vanadium-titanium slag, 20 parts by weight of cement, 12 parts by weight of lime, 6 parts by weight of gypsum, 0.12 parts by weight of aluminum powder, and 0.04 parts by weight of foam stabilizer; the raw material specifications are the same as in Example 1. Vanadium-titanium slag pretreatment: After magnetic separation, add grinding aid accounting for 4% of the vanadium-titanium slag mass, and grind for 4 hours until the specific surface area reaches 450 m². 2 / kg.

[0081] Raw material mixing: Dry mix for 4 minutes, add water (45% of total material mass) and stir for 6 minutes.

[0082] Aluminum powder and foam stabilizer treatment: Same as in Example 1.

[0083] Pouring and gas generation: Allow to stand for 1.5 hours at a temperature of 25℃ and a relative humidity of 70%.

[0084] Cutting: Cutting the blank according to specifications.

[0085] Autoclaving: The pressure was increased to 1.3 MPa at a rate of 0.15 MPa / h and maintained for 7 hours. After depressurization, the blocks were removed. Testing showed that the compressive strength of the blocks was 6.5 MPa and the thermal conductivity was 0.13 W / (m·K).

[0086] Example 3

[0087] Raw material preparation: Weigh out 70 parts by weight of vanadium-titanium slag, 15 parts of cement, 10 parts of lime, 8 parts of gypsum, 0.15 parts of aluminum powder, and 0.05 parts of foam stabilizer; the raw material specifications are the same as in Example 1.

[0088] Vanadium-titanium ore slag pretreatment: After magnetic separation, add grinding aid at 5% of the vanadium-titanium ore slag mass, grind for 5 hours, and achieve a specific surface area of ​​500 m². 2 / kg.

[0089] Raw material mixing: dry mix for 5 minutes, add water (50% of the total mass of materials) and stir for 8 minutes.

[0090] Aluminum powder and foam stabilizer treatment: Same as in Example 1.

[0091] Pouring and gas generation: Let it stand for 2 hours at a temperature of 30℃ and a relative humidity of 80%.

[0092] Cutting: Cutting the blank according to specifications.

[0093] Autoclaving: The pressure was increased to 1.5 MPa at a rate of 0.2 MPa / h and maintained for 8 hours. After depressurization, the blocks were removed. Testing showed that the compressive strength of the blocks was 7.8 MPa and the thermal conductivity was 0.12 W / (m·K).

[0094] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for producing lightweight concrete blocks for walls using vanadium-titanium ore slag, characterized in that, The process includes the following steps: Step 1: Weigh the raw materials, which consist of vanadium-titanium slag, cement, lime, gypsum, aluminum powder, and a foam stabilizer; Step 2: Grind the vanadium-titanium slag and grinding aid in a ball mill; Step 3: Mix the cement, lime, gypsum, aluminum powder, foam stabilizer, and the vanadium-titanium slag obtained in Step 2 in a mixer to obtain a mixed powder; mix the aluminum powder and foam stabilizer with water to obtain a suspension; Step 4: Mix the mixed powder and water to obtain a uniform slurry, then add the suspension and continue stirring to ensure that the aluminum powder is evenly dispersed in the slurry; Step 5: Pour the slurry obtained in Step 4 into a mold and allow it to stand and generate gas, causing the slurry to expand and form a blank containing uniform pores; Step 6: Cut the blank to obtain lightweight concrete blocks. Before step 1, the following steps are included: Step a: Directly guide the liquid titanium-type blast furnace slag discharged from the blast furnace into the slag mold; Step b: Air-cool the titanium-type blast furnace slag in the slag mold, so that a slag shell forms on the surface of the liquid titanium-type blast furnace slag in the slag mold as an isolation layer; Step c: Spray cool the titanium-type blast furnace slag with the slag shell on the surface to obtain solid slag blocks; Step d: Crush the solid slag blocks to obtain vanadium-titanium ore slag; The casting mold includes a mold cavity, a coolant circulation pipe, an inner baffle, a coolant connecting pipe, a water supply magnetic suction sleeve, and a water supply magnetic suction ring. The coolant circulation pipe is located inside the mold cavity and its axis is perpendicular to the bottom wall of the mold cavity. The top of the coolant circulation pipe is closed, and the bottom is open. The inner baffle is located in the coolant circulation pipe and is arranged along the axis of the coolant circulation pipe. There is a gap between the top of the inner baffle and the top of the coolant circulation pipe, dividing the hot-drain straight pipe into an inlet rectangular pipe, a top connecting pipe, and an outlet rectangular pipe connected in sequence. When spray cooling is performed, cooling water is supplied to the coolant circulation pipe, and the cooling water flows through the inlet rectangular pipe, the top connecting pipe, and the outlet rectangular pipe. The coolant connecting pipe includes a symmetrically arranged water supply rectangular pipe and a water drain rectangular pipe. The water supply rectangular pipe has an outlet... The liquid end is sealed to the liquid inlet rectangular pipe, and the liquid inlet end of the drain rectangular pipe is sealed to the liquid outlet rectangular pipe. The bottom of the coolant circulation pipe protrudes from the bottom of the mold cavity. The water supply magnetic ring is located at the bottom of the mold cavity. The bottom of the coolant circulation pipe passes through the bottom of the mold cavity and the water supply magnetic ring and protrudes from the water supply magnetic ring. The water supply sealing sleeve is fitted on the outer wall of the coolant connecting pipe and is slidably connected to the coolant connecting pipe. When the slag mold moves to the bottom of the spray unit, the coolant circulation pipe and the coolant connecting pipe are positioned accordingly. Then, the water supply magnetic sleeve is energized and magnetically attracted to the water supply magnetic ring, causing the water supply magnetic sleeve to move towards the coolant circulation pipe and fit at the connection between the coolant circulation pipe and the coolant connecting pipe. The coolant circulation pipe and the coolant connecting pipe are sealed together.

2. The method for producing lightweight concrete blocks for walls using vanadium-titanium slag according to claim 1, characterized in that, In step 1, the particle size of the vanadium-titanium slag is less than 0.15 mm.

3. The method for producing lightweight concrete blocks for walls using vanadium-titanium ore slag according to claim 1, characterized in that, In step 1, the cement is silicate cement with a strength grade of not less than 42.

5.

4. The method for producing lightweight concrete blocks for walls using vanadium-titanium slag according to claim 1, characterized in that, In step 1, the effective calcium oxide content of the lime is not less than 80%.

5. The method for producing lightweight concrete blocks for walls using vanadium-titanium slag according to claim 1, characterized in that, In step 2, the mass ratio of the grinding aid to the vanadium-titanium slag is 3~5:

100.

6. The method for producing lightweight concrete blocks for walls using vanadium-titanium ore slag according to claim 1, characterized in that, In step 3, dry mixing takes 3 to 5 minutes.

7. The method for producing lightweight concrete blocks for walls using vanadium-titanium slag according to claim 1, characterized in that, In step 4, the mass ratio of the mixed powder to water is 40~50:

100.

8. The method for producing lightweight concrete blocks for walls using vanadium-titanium slag according to claim 1, characterized in that, In step 5, the temperature for static gas generation is 20℃~30℃.

9. The method for producing lightweight concrete blocks for walls using vanadium-titanium slag according to claim 1, characterized in that, In step 5, the relative humidity is 60%~80%.

10. The method for producing lightweight concrete blocks for walls using vanadium-titanium slag according to claim 1, characterized in that, The standing time for gas generation is 1 to 2 hours.